Engineering practices for milk products : dairyceuticals, novel technologies, and quality - Goyal, Megh Raj; Hati, Subrota (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2019)
"While also addressing the need for more effective processing technologies for increased safety and quantity, the dairy industry needs to address the growing customer demand for new and innovative dairy foods with enhanced nutritional value. This volume, Engineering Practices for Milk Products: Dairyceuticals, Novel Technologies, and Quality, looks at new research, technology, and applications in the engineering of milk products, specifically covering functional bioactivities to add value while increasing the quality and safety of milk and fermented milk products. Chapters in the book look at the functional properties of milk proteins and cheese, functional fermented milk-based beverages, biofunctional yoghurt, antibiotic resistant pathogens, and other probiotics in dairy food products. The information found here will be of value to the growing dairy industry in India, globally the largest milk producing country since 1997, and the research will also be useful for dairy food engineering professionals wherever milk and dairy products are produced and consumed."--
Functional Properties of Milk Proteins / Veena Nagarajappa, Neelam Upadhyay, Rekha Chawla, Santosh Kumar Mishra, and B. Surendra Nath -- Composite Dairy Foods: Scope, Applications, and Benefits. / Rekha Chawla, Santosh Kumar Mishra, and Veena Nagarajappa -- Functionality Enhancement in Cheese / Apurba Giri and S. K. Kanawjia -- Emerging Trends in Concentration and Drying of Milk and Milk Products / Sunil Kumar Khatkar, Jashandeep Kaur, Anju B. Khatkar, Narender Kumar Chandla, Anil Kumar Panghal, and Gurlal Singh Gill -- Technological and Biochemical Aspects of Ghee (Butter Oil) / Pinaki Ranjan Ray -- Functional Fermented Milk-Based Beverages / Narendra Kumar and Vandna Kumari -- Biofunctional Yogurt and Its Bioactive Peptides / Jagrani Minj, Subrota Hati, Brij Pal Singh, and Shilpa Vij -- Antibiotic Resistant Pathogens in Milk and Milk Products / Ami Patel, Falguni Patra, and Nihir Shah -- Quality and Safety Management in the Dairy Industry / Kunal M. Gawai and V. Sreeja -- Genetic Improvement of Dairy Starter Cultures and Lactic Acid Bacteria / Lopamudra Haldar and Soumyashree Saha -- Metabolic Engineering of Lactic Acid Bacteria (LAB) / Mital R. Kathiriya, J.B. Prajapati, and Yogesh V. Vekariya -- Metabolites of Lactic Acid Bacteria (LAB) for Food Biopreservation / Santosh Kumar Mishra, Rekha Chawla, Veena Nagarajappa, and Krishan Kumar Mishra -- Shelf-Life Extension of Fermented Milk Products / V. Sreeja and Kunal M. Gawai -- Probiotics: From Science to Technology / Vandna Kumari and Narendra Kumar -- Applications of Probiotics in Dairy Food Products / Divyasree Arepally, Sudharshan Reddy Ravula, and Tridib Kumar Goswami
OCLC-licensed vendor bibliographic record.
Keywords: Dairy products industry -- Technological innovations; Dairy products; SCIENCE / General; TECHNOLOGY / Agriculture / Animal Husbandry; TECHNOLOGY / Food Science